Rationalization of liability for endeavor of committing of crime (between objective and subjective theory) - Marciniak, Beata (Acta Universitatis Lodziensis. Folia Iuridica, 2015)
Penal liability for stages of perpetrating an offence is not an unambiguous issue. So, it must be remembered that in case of endeavor there is no infringement of the legal interest, or if clumsy endeavor is meant such infringement could not take place. Expansion of penality beyond perpetration, is substantiated in literature by actual social harmfulness of such behavior which is not indifferent from the point of view of their negative importance in a social sense. Each endeavor means endangering the legal interest protected by a proper legal ban; in case of endeavor the danger is direct. So, penality of endeavor is justified by two elements.